Inducible DNA Cross-Linking Agents: Design, Synthesis, Mechanism, and Anticancer Activity - (:unkn) unknown (My University, 2018)
This thesis focuses on investigating the reactivity of DNA towards a wide variety of aromatic compounds as novel DNA cross-linking agents and exploring their biomedical applications. In the first part, we synthesized three series of bifunctional aromatic compounds with various core structures, aromatic substituents, and benzylic leaving groups and investigated their reactivity towards DNA. Most of these compounds efficiently form DNA interstrand cross-links (ICLs) via carbocations generated upon irradiation at 350 nm. The efficiency of DNA ICL formation and the pathway of carbocation formation strongly depend on core structures, aromatic substituents and leaving groups. Mono benzene analogues bearing an electron donating substituent showed higher DNA cross-linking efficiency than those with an electron withdrawing substituent while an opposite trend was observed for the biphenyl compounds. In most cases the carbocations were generated through oxidation of the corresponding benzyl radicals. However, photo irradiation of the ammonium salt 5b generated the carbocation via direct heterolysis of the C-N bond. Surprisingly, both path ways were observed for compound 4b. The second part is in vivo efficacy study of H2O2-activated quinone methide (IIi, IIIa) and nitrogen mustard (IVq) precursors. Compounds IIi and IIIa inhibited the tumor growth in nude mice xenografted with MDA-MB-468 breast cancer cells without obvious toxicity, such as no weight loss and other unusual behaviors, while they were less effective towards renal cancer cells. Compound IVq greatly shrank the tumor size in nude mice xenografted with MDA-MB-468. The third part focused on investigating the influences of triazole-moieties and the substituents at the position-4 of triazole ring on the thermal stability of DNA duplexes by testing the melting temperature of the DNA•DNA and DNA•RNA duplexes containing triazole-modified thymidines (41-43). The introduction of triazole-modified thymidines decreased the stability of DNA•DNA and DNA•RNA duplexes. Bulky substituent at the position-4 of triazole ring further destabilized DNA duplex possibly due to steric hindrance interfering with efficient Watson-Crick base-pair formation. Due to noncoplanar conformation between substituents and thymine groups, two or three consecutive modifications further destabilized the DNA duplex even in the presence of efficient π-stacking induced by modified-triazole moieties